Public health programmes to promote mental health in young people: a systematic integrative review protocol - Mihiri Chami Wettasinghe; Nuwan Darshana Wickramasinghe; Tine Van Bortel; Antony Morgan; Antonis A Kousoulis; Nelum Samarutilake; Julie Feiler (BMJ Open)
Introduction In light of the ever-growing mental health disease burden among young people worldwide, we aim to systematically review the global literature to identify the public health programmes targeted at promoting mental health and well-being in young people, the reported/anticipated mental health-related outcomes of the implemented public health programmes and the reported facilitators and barriers in relation to the implementation of those public health programmes.Methods and analysis A comprehensive literature search will be carried out in the following electronic bibliographic databases: MEDLINE, EMBASE, PsycINFO, Scopus, ASSIA, Web of Science, Global Health, AMED, Health Source and The Cochrane Library. Further, a manual search of the reference lists of eligible studies and reviews will be carried out. The search strategy will include combinations of three key blocks of terms, namely: ‘young people’, ‘mental health’ and ‘public health programme’, using database-specific subject headings and text words. Two reviewers will independently screen, assess data quality and extract data for synthesis. Disagreements at any stage will be resolved by consensus with the involvement of a third reviewer. Given the anticipated methodological pluralism of the potential eligible studies, we will provide a narrative synthesis of the findings on public health programmes aimed at promoting the mental health and well-being of young people according to identified thematic areas. Furthermore, a narrative synthesis of the reported facilitators and barriers in relation to the implementation of public health programmes will be provided.Ethics and dissemination Given that the review findings will be focused on understanding the breadth and depth of the global research into public health programmes to promote mental health in young people with a particular emphasis on the facilitators and barriers of programmatic implementation, the findings will be of great value to inform future interventions, programmes and approaches to promote mental health and well-being of young people worldwide.PROSPERO registration number CRD42018099551.